From troops to teachers: changing careers and narrative identities. Issue 3 (27th May 2019) - Price, Mark
ABSTRACT: Troops to Teachers (TtT) is a UK governmental scheme introduced in 2013 to facilitate ex-military service personnel to re-train as teachers. This narrative study explores the accounts of a sample of new TtT trainees at the onset of their training and considers their motivations for career changing, potential transferable attributes and skills, aspirational teacher identities and anticipated challenges. Emerging from these rich narratives is a strong, shared commitment to the trainees' chosen new career. Self-discipline is identified as a professional quality to take into teaching from military service, whilst maintaining discipline in the classroom is more commonly regarded as an area of concern and challenge, rather than as a transferable skill set, challenging core governmental expectations of the Troops to Teachers initiative. However, the importance of and a desire and commitment to continue to 'serve', is widely held, reflecting a particular narrative refraction of the TtT trainees. This provides potential for further, perhaps longitudinal study, as the troops become teachers. The study affirms the potential for further investment in a wider recruitment strategy for career-change teachers more generally, as providing an experienced and motivated professional workforce for schools. Abbreviation DfE: Department for Education; MoD: Ministry of Defence; TtT: UK Troops to Teachers; TTT: USA Troops To Teachers